Kajian Konseptual Evaluasi Instrumen Tes Potensi Akademik Berbasis CBT pada Seleksi Masuk Perguruan Tinggi - Mutiara Lestari; Aprillia Zara; Allisa Kirana; Syifa Miranda Amir (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The transition from paper-based to Computer-Based Test (CBT) in the Academic Potential Test (TPA) for state university entrance selections has significantly transformed the educational assessment landscape. This conceptual study aims to evaluate the instruments of CBT-based TPA, focusing on validity, reliability, fairness, and technological infrastructure constraints. Employing a systematic literature review approach, this research synthesizes various foundational theories of educational measurement, specifically Item Response Theory (IRT) and Computerized Adaptive Testing (CAT), alongside contemporary empirical findings from the last five years. The findings indicate that while CBT offers enhanced administrative efficiency and rapid grading, the validity of the instruments is frequently challenged by item exposure and the diverse digital literacy levels of test-takers. Furthermore, infrastructural disparities among regions pose a significant threat to testing fairness. The implication of this study suggests the urgent need for a dynamic item bank generation system and the implementation of adaptive testing to mitigate cheating and ensure equitable assessment. Future educational policies must bridge the digital divide before uniformly mandating CBT. Ultimately, this review provides a comprehensive framework for test developers to refine CBT TPA instruments, ensuring they genuinely measure academic potential rather than technological proficiency.